Biosorption of Cadmium by Filamentous Fungi Isolated from Coastal Water and Sediments. (22nd October 2018) - Manguilimotan, Lebeth C.; Bitacura, Jayzon G.
Abstract : The use of microorganisms in decontaminating the environment encumbered with heavy metal pollutants through biosorption is considered as a good option for bioremediation. This study was conducted to isolate Cadmium (Cd) tolerant fungi from coastal waters and sediments, compare their biosorption capabilities, and identify the isolates with the highest Cd uptake. Water and sediment samples were collected near the effluent sites of industrial belt in Ibo, Lapu-lapu City, Cebu, Philippines. Potato dextrose agar (PDA) plates containing Cd (25, 50, 75, and 100 ppm) were used to isolate Cd tolerant fungi from the samples. The distinct colonies that grew on the highest Cd concentration (100 ppm) were then isolated into pure cultures. The pure cultures of Cd tolerant fungi served as a source of inocula for in vitro biosorption assay using Cd dissolved in potato dextrose broth (PDB) as the substrate. Cd tolerant fungal isolates with the highest Cd uptake were finally identified up to the lowest possible taxon based on their colonial and microscopic characteristics. Most filamentous fungal colonies have grown most at the lower Cd concentrations and least at the higher concentrations. From the characteristics of the fungal growth on the plate with the highest Cd concentration, eight distinct colonies from both sediment and water samples were isolated into pure cultures. Among the eight fungal isolates, only three had significant Cd biosorption efficiency, these were fungal isolate 3 (13.87 %), fungal isolate 6 (11.46 %), and fungal isolate 4 (10.71 %). Two of them (fungal isolates 3 and 4) belong to genus Aspergillus while the other (fungal isolate 6) is a species of Penicillium . The results of this study showed that Cd tolerant fungi with biosorption capacity could be isolated from coastal water and sediments in the vicinity of areas suspected of heavy metal contamination.